Strategi Pengelolaan Homestay Melalui Penerapan Chse dan Pemanfaatan Digitalisasi Media Sosial di Desa Wisata Purwosari - Phia Susanti Helyanan; Adiya Narindra Pratiwi; Binti Khabibatul Zulfa; Dian Ayu Permatasari; Lintang Jati Maharani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Increasing tourism businesses, especially homestays, is a tourist need while in tourist destinations, so that services and comfort are needed during the Covid-19 pandemic. This study identified several homestay problems including: the requirements to become a homestay, how to develop a homestay (CHSE standard), homestay administration and digital use with social media. The purpose of this study is to increase public understanding of homestay SOPs, online check-in/out administration of tourists while staying at homestays and promotions through Instagram. The method used is counseling, discussion and short practice. Research Results Good resource management in homestay management, effective administration through google forms, and effective ways of promotion during the pandemic through Instagram will support the homestay business in Purwosari village to increase and be able to survive during the covid-19 pandemic.